Study on the Use of CT Ring Protection as Back Up Protection For Overcurrent Disruptions in PLN Distribution Network System - Sadikin, Firman; Sudiarto, Ing. Budi (Budapest International Research in Exact Sciences (BirEx) Journal, 2024)
Protection is a safeguard in the electric power system installed in the electric power distribution system, power transformers, electric power transmission, and electric generators used to protect the electric power system from electrical disturbances or overloads by separating the disturbed part of the electric power system from the existing electric power system. Not disturbed so that the uninterrupted electrical system can continue to work. Failure of the protection system at the KG02 and KG 180 substations at PT PLN (Persero) UP3 Tanjung Priok when short circuit currents occurred on the phases on the consumer side resulted in the PMT (Power Breaker) of the feeder tripping. This resulted in widespread outages which had a negative impact on the image of PT PLN (Persero) UP3 Tanjung regarding network reliability. To find out the cause of the protection system failure, CT (Current Transformer) checks were carried out on the three substations. At the KG02 substation, the 345KVA CT power contract is installed with a ratio of 10/5 and class 5P10 with a fault current of 2861A. At the KG180 substation, the CT is installed with a ratio of 100/5 with class 5P10 with a fault current of 6547A. From the results of the data from the two substations above, the protection system failure occurred in the current transformer which was saturated when a fault current exceeded 2861A and 6547A. To overcome protection failures at the two substations above, it is necessary to add a CT Ring 800/5 with class 5P20, with the test results being a reference for improving the protection system so that similar failures do not happen again.